2010
DOI: 10.1111/j.1365-2648.2010.05293.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity among adolescents: sedentary leisure time and sleeping as determinants

Abstract: To help prevent obesity, strategies are needed to decrease adolescents sedentary leisure time and help them have sufficient sleep. Nurses can play a key role in health promotion in relation to childhood and adolescent obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 45 publications
4
54
1
1
Order By: Relevance
“…112 Early sleep patterns may influence BMI in adolescents and young adults as well. Longitudinal data suggest that children who sleep less, have later bedtimes, or get up earlier subsequently have higher BMIs and are more likely to be overweight, even after controlling for baseline BMI.…”
Section: Insufficient Sleep and Obesity Riskmentioning
confidence: 99%
“…112 Early sleep patterns may influence BMI in adolescents and young adults as well. Longitudinal data suggest that children who sleep less, have later bedtimes, or get up earlier subsequently have higher BMIs and are more likely to be overweight, even after controlling for baseline BMI.…”
Section: Insufficient Sleep and Obesity Riskmentioning
confidence: 99%
“…1 Recent research has identified associations between various time use patterns and both physical and psychological health outcomes. [2][3][4][5][6] There is compelling evidence to suggest that socioeconomic position (SEP), particularly household income, is positively associated with child and adolescent health. 7 Youth health interventions are unlikely to alter parental income, but SEP-related time use behaviours are potentially modifiable.…”
mentioning
confidence: 99%
“…In adolescence there is less inhibition of the secretion of melatonin at the beginning of the light phase of the day and a slower accumulation of the tendency to sleep during the day, which may lead to a phase delay, more commonly observed in more advanced pubertal periods [24]. Thus, the biological and behavioral changes that occur during adolescence lead to a phase delay that, according to the social and school context, will reflect on a reduction of hours of sleep and an increase in daytime somnolence [25,26].…”
Section: Physiology Of the Sleep-wake Cyclementioning
confidence: 99%